Claviceps arundinis identification and its role in the die-back syndrome of Phragmites australis populations in central Italy. (4th July 2018) - Cerri, M.; Reale, L.; Moretti, C.; Buonaurio, R.; Coppi, A.; Ferri, V.; Foggi, B.; Gigante, D.; Lastrucci, L.; Quaglia, M.; Venanzoni, R.; Ferranti, F.
Abstract: Common reed Phragmites australis (Cav.) Trin. ex Steud. is one of the most widely distributed angiosperms with important ecological functions. In recent decades, it has been affected by a severe decline known as reed die-back syndrome (RDBS), the causal factors of which are still under investigation. Among the biotic factors that influence the dynamic of the reed population, the role of microorganisms is still poorly understood. During surveys carried out on P. australis populations in Central Italy, Claviceps -like sclerotia were detected: is Claviceps infection related to P. australis sexual reproduction and seed production? Could Claviceps infection be involved in the RDBS ? These are the questions that we address. We characterized the sclerotia at the morphological, molecular, and chemical level and we demonstrated that they belong to Claviceps arundinis Pažoutová & M. Kolařík. To our knowledge, this is the first report of C. arundinis on P. australis in Italy. Furthermore, the association of C. arundinis with RDBS was evaluated considering a set of macromorphological traits generally related to RDBS, such as P. australis clumping habit, culm height and diameter. No correlation was seen between the occurrence of C. arundinis and the declining status of reed populations.